Helicobacter pylori caga induces cortactin y-470 phosphorylation-dependent gastric epithelial cell scattering via abl, vav2 and rac1 activation - Tegtmeyer, Nicole; Harrer, Aileen; Rottner, Klemens; Backert, Steffen (Cancers, 2021)
The pathogen Helicobacter pylori is the first reported bacterial type-1 carcinogen playing a role in the development of human malignancies, including gastric adenocarcinoma. Cancer cell motility is an important process in this scenario, however, the molecular mechanisms are still not fully understood. Here, we demonstrate that H. pylori subverts the actin-binding protein cortactin through its type-IV secretion system and injected oncoprotein CagA, e.g., by inducing tyrosine phosphorylation of cortactin at Y-470, which triggers gastric epithelial cell scattering and motility. During infection of AGS cells, cortactin was discovered to undergo tyrosine dephosphorylation at residues Y-421 and Y-486, which is mediated through inactivation of Src kinase. However, H. pylori also profoundly activates tyrosine kinase Abl, which simultaneously phosphorylates cortactin at Y-470. Phosphorylated cortactin interacts with the SH2-domain of Vav2, a guanine nucleotide exchange factor for the Rho-family of GTPases. The cortactin/Vav2 complex then stimulates a previously unrecognized activation cascade including the small GTPase Rac1, to effect actin rearrangements and cell scattering. We hypothesize that injected CagA targets cortactin to locally open the gastric epithelium in order to get access to certain nutrients. This may disturb the cellular barrier functions, likely contributing to the induction of cell motility, which is important in gastric cancer development.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cancer; Cortactin; Helicobacter; Pathogenesis; Pathogenicity island; Signaling; Virulence